The Influence of Service Quality Dimensions on Customer Satisfaction in Mr. Geprek MSME - Pratama, Muhammad Arkana Alzair; Ambarwati, Dwi Asri Siti (LPPPIPublishing, 2025)
This study investigates how service quality dimensions influence customer satisfaction at Mr. Geprek, a culinary Micro, Small, and Medium Enterprise (MSME) at Lampung University. Small and Medium Enterprises significantly contribute to Indonesia's GDP and employment but face challenges in competitiveness, particularly regarding customer satisfaction. Service quality, encompassing tangibles, reliability, responsiveness, assurance, and empathy (SERVQUAL model), is crucial for business success. While previous research often focused on larger firms, this study specifically examines a student-run MSME and incorporates the impact of technology. Employing a quantitative research approach with an explanatory and descriptive design, the study collected primary data from 100 Mr. Geprek customers at Lampung University using Google Forms surveys and a 5-point Likert scale. Data analysis was performed using IBM SPSS Statistics 27, including descriptive analysis, multiple linear regression, F-tests, and t-tests.